The Choice of Funding Sources for Start-Ups in a Transitional Economy: The Ability to Predict in a National Context - Olga Obraztsova; Tatiana Poliakova; Ekaterina Popovskaya (Foresight and STI Governance)
Despite the government’s efforts to support entrepreneurship, the major share of start-up funding in transitional economies comes from the owners’ own funds and ‘‘love capital’’ rather than from institutional sources (banks, venture funds, etc.). This increases the asymmetry of information concerning the capabilities of the emerging businesses for potential investors, and thus hinders the development of entrepreneurship as a whole. The paper considers the key determinants affecting the decisions made by entrepreneurial start-ups when choosing from a number of ways to finance their business in transitional economies. An attempt has been made to build models for an adequate prediction of the financial strategies of early entrepreneurs. A number of hypotheses have been put forward to verify external and internal factors influencing the financial choices of early entrepreneurs. Hypotheses were tested on a survey sample of early entrepreneurs from seven transitional economies, including Russia. The predictive values of the final models proved to be effective in predicting start-ups’ financial strategies and in comparing the probability of early entrepreneurs borrowing capital. Our findings confirm that the combinations of external and internal financing differ significantly depending on the national macroeconomic and social context. Given that simple borrowing mechanisms for supporting a business can lead to an undesirable tendency to avoid formal borrowed funds altogether, such behavior can hinder the development of entrepreneurship. The obtained results show that pessimistic short-term expectations about the conditions for entrepreneurship in a region aggravate this problem in Russia. The outcomes demonstrate a need to reduce the burden on start-up businesses and to improve innovative entrepreneurial aspirations by encouraging high confidence in a start-up’s future and find the optimal proportion of borrowed sources in a business’s capital structure.